2021
DOI: 10.1021/acsami.1c16096
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework-Derived Tubular In2O3–C/CdIn2S4 Heterojunction for Efficient Solar-Driven CO2 Conversion

Abstract: Realizing high-efficiency solar-driven CO2 reduction to chemicals and fuels requires high-performance photocatalysts with high utilization efficiency of solar light, efficient charge separation and transfer, and robust adsorption capacity for CO2. In this work, a tubular In2O3–C/CdIn2S4 (IOC/CIS) ternary heterojunction with an intimate interfacial contact was fabricated by pyrolysis of In-MIL-68 and subsequent solvothermal synthesis of CdIn2S4. The construction of a heterojunction promotes the separation and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 57 publications
(101 reference statements)
0
18
0
Order By: Relevance
“…The flat band potentials of g-C 3 N 4 and IT obtained from the intercepts on the x axis are −1.02 and −0.86 V (vs NHE, pH = 7) (Figure a,b), respectively. From the literature, the flat band potential is about 0.1 V positive than the conduction band (CB) potential, so the CB values of g-C 3 N 4 and IT are −1.12 and −0.96 V (vs NHE, pH = 7), respectively. These CB values are higher than the reduction potential (−0.53 V) of CO 2 to CO, fulfilling the thermodynamic requirement of such a reaction .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flat band potentials of g-C 3 N 4 and IT obtained from the intercepts on the x axis are −1.02 and −0.86 V (vs NHE, pH = 7) (Figure a,b), respectively. From the literature, the flat band potential is about 0.1 V positive than the conduction band (CB) potential, so the CB values of g-C 3 N 4 and IT are −1.12 and −0.96 V (vs NHE, pH = 7), respectively. These CB values are higher than the reduction potential (−0.53 V) of CO 2 to CO, fulfilling the thermodynamic requirement of such a reaction .…”
Section: Resultsmentioning
confidence: 99%
“…41 For example, Wang et al synthesized a sandwich-like In 2 O 3 −ZnIn 2 S 4 tubular heterojunction from MIL-68-(In) with excellent performance on CO 2 photocatalytic reduction, 42 and Zhao et al reported on utilizing MOFs for the construction of carbon-coated ITs with CdIn 2 S 4 . 43 Nevertheless, it is still challenging to incorporate metal-free polymer semiconductors into MOF derivatives with compact and intimate particle arrangements. In our work, the MOF enabled the formation of a compact and staggered arrangement between g-C 3 N 4 and In 2 O 3 , maximizing direct contact between the phases for improved charge separation across the interface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…20,21 CdIn 2 S 4 , as an example of a chalcogenide semiconductor with a narrow band gap, has been widely researched because of its applications in various fields. 22,23 However, CdIn 2 S 4 has some limitations in practical applications, such as the high recombination efficiency of photogenerated electron–hole (e − –h + ) pairs, a narrow visible-light response range, and a limited number of active sites. These drawbacks limit its application in the photocatalytic selective oxidation of biomass platform molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The In 2 O 3 −C/CdIn 2 S 4 heterojunction performed outstanding photocatalytic activity toward CO 2 reduction. 32 Han et al fabricated a N-doped C-encapsulated In 2 O 3 −In 2 S 3 hollow dodecahedral heterostructure by sulfurization followed by carbonization of In-MOF and investigated their photocatalytic activity toward production of value-added chemicals. 33 Dai et al prepared a carbon-coated In 2 O 3 / ZnIn 2 S 4 hollow tubular heterostructure by calcination of MIL-68 (−NH 2 ) under N 2 atmosphere followed by a hydrothermal synthesis of ZnIn 2 S 4 .…”
Section: Introductionmentioning
confidence: 99%
“…have synthesized In 2 O 3 –C/CdIn 2 S 4 heterojunction photocatalytic materials by pyrolysis of MIL-68 under inert atmosphere followed by solvothermal synthesis of CdIn 2 S 4 . The In 2 O 3 –C/CdIn 2 S 4 heterojunction performed outstanding photocatalytic activity toward CO 2 reduction . Han et al fabricated a N-doped C-encapsulated In 2 O 3 –In 2 S 3 hollow dodecahedral heterostructure by sulfurization followed by carbonization of In-MOF and investigated their photocatalytic activity toward production of value-added chemicals .…”
Section: Introductionmentioning
confidence: 99%